PEAT CARBON, CIRE AND CLIMATE INTERACTIONS - Aldrian, Edvin (Jurnal Hidrosfir Indonesia, 2008)
This study describes the interaction between forest fire and climate, which focuses on the peatland fire contribution and its carbon released. We established the interannual carbon released that refer to some previous result and we extend the results for the last decade(1997 to 2007) of total carbon and PM10 estimations. We found a significant relationship betweenclimate and hotspot number, which indicate the behavior of fires over Sumatera and Kalimantan over the last decade, except for 2006. Improvement in the correlation occurs when we utilized second half of the year in to consideration. Apparently there are two regional climatic systemsthat drive or force the annual variability of hotspots over Sumatera and Kalimantan through trans equatorial cold surge in the first half of year and El Nino in the second half of the year. The cold surge phenomenon is crucial for the hotspot variability for Riau province, while the latter could impacts both Sumatera and Kalimantan. Strong climate forcing indicates, by excluding 2006, that Indonesian peat pool is vulnerable to the regional climatic system or a victim of regional climate perturbation. Recent data (latest four years) shows larger fluctuation from the climatic factor. The 2006 fires and their emission are exceptionally high and divert from the strong correlation between fire and climatic factor. The 2006 fire close to 1997 firein amount and emission (88.4%) and PM10 (87%) and hotspot number (92.8%). Overall, during the last decade, the carbon emission from forest fires in Indonesia fluctuates following climate variability and could not be generalized to emit carbon at persistently high level every year.